2015
DOI: 10.1002/jeab.177
|View full text |Cite
|
Sign up to set email alerts
|

When good pigeons make bad decisions: Choice with probabilistic delays and outcomes

Abstract: Pigeons chose between an (optimal) alternative that sometimes provided food after a 10-s delay and other times after a 40-s delay and another (suboptimal) alternative that sometimes provided food after 10 s but other times no food after 40 s. When outcomes were not signaled during the delays, pigeons strongly preferred the optimal alternative. When outcomes were signaled, choices of the suboptimal alternative increased and most pigeons preferred the alternative that provided no food after the long delay despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 47 publications
5
29
0
Order By: Relevance
“…Although there is a growing body of evidence to suggest that losses minimally influence preferences by pigeons 30, 34, 35 , translational procedures with rats have suggested that, if there is inhibition to loss signals, suboptimal choice does not occur 46 , and humans may show differential discounting of wins and losses 21, 22 . Although the lack of the ‘jackpot’ signal appearing on loss trials likely serves as a signal for a loss, we introduced a more salient signal for loss outcomes in the Signaled group to determine if salient losses would influence discount rates (see supplemental materials).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a growing body of evidence to suggest that losses minimally influence preferences by pigeons 30, 34, 35 , translational procedures with rats have suggested that, if there is inhibition to loss signals, suboptimal choice does not occur 46 , and humans may show differential discounting of wins and losses 21, 22 . Although the lack of the ‘jackpot’ signal appearing on loss trials likely serves as a signal for a loss, we introduced a more salient signal for loss outcomes in the Signaled group to determine if salient losses would influence discount rates (see supplemental materials).…”
Section: Resultsmentioning
confidence: 99%
“…In this suboptimal choice procedure, choice of a gambling-like alternative is followed either by a signal indicating that a win or loss will follow, while the alternative choice generally results in an ambiguous, uninformative cue that provides greater overall reward 26 . It has been hypothesized that under these conditions pigeons over-weight the infrequent signal for wins 28, 29 , and show more optimal preferences if these signals are ambiguous 32, 33 ; conversely, pigeons also appear to under-weight the signal for losses 30, 31, 34, 35 , and show little change in choice when the salience of the loss is manipulated 30, 35 . Similar effects involving signaled outcomes may also be relevant to human risk taking, as Molet et al .…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the present study is the first to obtain suboptimal choice behavior in rats using a suboptimal choice procedure commonly used with pigeons (Pisklak et al 2015; McDevitt et al 2016; Zentall, 2016; Smith and Zentall, 2016; Smith et al 2016) and replicated with humans (Molet et al 2012). Importantly, like previous studies using lights as terminal-link stimuli to assess suboptimal choice behavior in rats using a similar procedure (Roper and Baldwin, 2004; Trujano and Orduna, 2015; Trujano et al 2016), we also demonstrated optimal choice behavior in rats when using lights as reward-associated stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous research (Fantino, 1969; Moore, 1985; Dunn and Spetch, 1990; Williams and Dunn, 1991; Mazur, 1991, 1995, 1997; Williams, 1994; Roper and Zentall, 1999; Stagner et al 2012; Pisklak et al 2015; Smith and Zentall, 2016; Smith et al 2016) has suggested the importance of terminal-link stimuli as conditioned reinforcers and their ability to influence choice through various approaches. On the contrary, other approaches have been used that closely resemble the procedure used herein and have found contrasting results leading to different theories on the mechanisms that drive suboptimal choice behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation